Intervención y rediseño interiorista de la zona de relajación del Club Recreacional Rancho San Vicente – Policía Nacional - Freire Mena, Samantha Michelle (2020)
The present degree project proposes to improve the current state of the relaxation area of ​​the Rancho San Vicente recreational club belonging to the National Police, providing spaces worthy of a respectable institution and in turn improving them with a natural design where the police and members in general They can relax before and after hard work, the project is aimed at young and old women and men. The Rancho San Vicente club is located in the province of Pichincha, Quito canton on Av. La Prensa, Av Brasil and Juan Galarza streets, the intervention was carried out in the club is relaxation area that has a reception, waiting room, bar, dining room, kitchen, entertainment area, bathrooms, stretching area, gym, massage room, nutrition office and wet area containing hydromassage, sauna, cold water shower and drawer baths with a total of 1118m2. The proposal carries out as a design concept the white lotus flower, which represents the total purity of the body and soul in order to achieve a natural and relaxing space, the concept is reflected with the color of the flower environment, organic forms, movement and essence. For the redesign, a new proposal of floor, walls, ceiling, lighting and furniture was made, natural and artificial vegetation was incorporated throughout the project, abandoned spaces were used in which new uses were proposed, open space design was proposed , the distribution was improved in order to create comfort and convenience for users. The proposal aims to improve the quality of life of the users who attend this complex to free themselves from work stress or take care of their physical and mental health in a space of absolute, elegant and functional relaxation.